A hybrid P3HT-Graphene interface for efficient photostimulation of neurons. (June 2020) - DiFrancesco, Mattia L.; Colombo, Elisabetta; Papaleo, Ermanno D.; Maya-Vetencourt, José Fernando; Manfredi, Giovanni; Lanzani, Guglielmo; Benfenati, Fabio
Abstract: Graphene conductive properties have been long exploited in the field of organic photovoltaics and optoelectronics by the scientific community worldwide. We engineered and characterized a hybrid biointerface in which graphene is coupled with photosensitive polymers, and tested its ability to elicit light-triggered neural activity modulation in primary neurons and blind retina explants. We designed such a graphene-based device by modifying a photoactive P3HT-based retinal interface, previously reported to rescue light sensitivity in blind rodents, with a CVD graphene layer replacing the conductive PEDOT:PSS layer to enhance charge separation. The new graphene-based device was characterized for its electrochemical features and for the ability to photostimulate primary neurons and blind retina explants, while preserving biocompatibility. Light-triggered responses, recorded by patch-clamp in vitro or MEA ex vivo, show a stronger light-transduction efficiency when the neurons are interfaced with the graphene-based device with respect to the PEDOT:PSS-based one. The possibility to ameliorate flexible photo-stimulating devices via the insertion of graphene, paves the way for potential biomedical applications of graphene-based neuronal interfaces in the context of retinal implants. Graphical abstract: Image 1